Specific Features of the Formation and Development of Mediation in Foreign Countries with Anglo-Saxon and Romano-Germanic Legal Systems (Law and Safety, 2020)
In the context of radical changes taking place in the field of jurisprudence, the topic of researching innovative forms of mediation, which has recently become a phenomenon of legal reality, becomes especially relevant. The scientific work is focused on studying the peculiarities of the formation and development of mediation in foreign countries with Anglo-Saxon and Romano-Germanic legal systems, as well as the procedure for training professional mediators in these countries. According to the chosen topic, the purpose of this scientific article is to consider the modern system of training mediators in developed countries with different legal systems, their comparative analysis in the context of common methods and techniques of training mediators in the world practice, with further implementation of international experience of developed countries in Ukraine, as well as perspectives for applying mediation as an independent way of resolving legal disputes in Ukraine.In accordance with the purpose and objectives of the research, the author of the scientific work has used a set of methods and techniques of scientific cognition, both general theoretical, special and scientific. Using the epistemological method of the research, the author has defined the essence of mediation as a separate alternative way of resolving disputes, which was initiated in the 60-70s of the XX century in the United States of America. Using the historical method, the author has studied the stages of development of mediation in foreign countries with Anglo-Saxon and Romano-Germanic legal systems. The comparative and legal method has been used to generalize international experience in the development of mediation and training of mediators in Ukraine, to develop recommendations for the introduction of such experience in the area of alternative dispute resolution along with litigation.The peculiarities of the stages of the formation and further development of the institution of mediation in foreign countries with Anglo-Saxon and Romano-Germanic legal systems have been analyzed. Based on the generalization of leading international practices, the author has conducted a brief overview of the training of mediators in countries with different legal systems. The expediency of introducing international experience of developed countries in the training of mediators in Ukraine has been substantiated. It has been concluded that the legislative consolidation of the institution of mediation in Ukraine by the example of developed countries with Anglo-Saxon and Romano-Germanic legal systems will provide rapid and cost-effective out-of-court settlement of disputes, as well as improve and simplify access to justice. It has been proved that on the basis of the model of mediation development in developed foreign countries, its introduction in Ukraine will allow to bring the provisions of national justice closer to European standards; reduce state budget expenditures, as well as promote the development and enhancement of the legal culture of citizens.
Keywords: mediation; mediators; intermediation; alternative dispute resolution; Anglo-Saxon legal system; Romano-Germanic legal system